2007
DOI: 10.1177/104063870701900211
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Orchitis and Epididymitis Caused by Salmonella Enterica Subspecies Diarizonae Infection in a Ram

Abstract: A case of unilateral suppurative epididymo-orchitis associated with Salmonella enterica subsp. diarizonae serovar 61:k:1,5,(7) infection is described in a 2-year-old ram. Gross lesions were characterized by severe enlargement of the scrotal contents, fibrous adhesions between testicular layers, coexistence of epididymal abscesses and foci of fibrinous exudate, and testicular atrophy. Microscopically, testicular and epididymal microabscesses and diffuse inflammatory infiltrates with abundant macrophages contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 16 publications
0
7
0
4
Order By: Relevance
“…SA S d is able to produce both intestinal and extra-intestinal infections with faecal, vaginal and nasal colonisation as well as shedding, but mostly without clinical disease [79]. However, it has also been reported that SA S d may occasionally cause rhinitis or chronic nasal inflammation [10, 11], orchitis [12], or aborted foetuses [4]. As these properties deviate from the classical characteristics of host-restricted, host-adapted or ubiquitous serovars [13], the term sheep associated serovar [6] appears most appropriate to characterise serovar 61: k: 1, 5, (7).…”
Section: Introductionmentioning
confidence: 99%
“…SA S d is able to produce both intestinal and extra-intestinal infections with faecal, vaginal and nasal colonisation as well as shedding, but mostly without clinical disease [79]. However, it has also been reported that SA S d may occasionally cause rhinitis or chronic nasal inflammation [10, 11], orchitis [12], or aborted foetuses [4]. As these properties deviate from the classical characteristics of host-restricted, host-adapted or ubiquitous serovars [13], the term sheep associated serovar [6] appears most appropriate to characterise serovar 61: k: 1, 5, (7).…”
Section: Introductionmentioning
confidence: 99%
“…The bacteria have been reported to be commonly found in sheep in the United Kingdom (UK), Norway and Switzerland [ 5 - 8 ]. The infection in sheep is usually sub-clinical [ 9 ] but may cause enteritis, rhinitis, orchitis, and aborted or stillborn foetuses [ 5 , 10 , 11 ]. SASd is only occasionally isolated from other species [ 12 ] and seldom reported in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Trypanosoma brucei, Salmonella enterica subsp. Diarizonae, Chlamydia spp also isolated from those cases of orchitis and peri-orchitis infection in a mature ram (6,(24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 91%